1998
DOI: 10.1021/bi9810205
|View full text |Cite
|
Sign up to set email alerts
|

Residues Critical for Formylglycine Formation and/or Catalytic Activity of Arylsulfatase A

Abstract: Sulfatases contain a unique posttranslational modification in their active site, a formylglycine residue generated from a cysteine or a serine residue. The formylglycine residue is part of a sequence that is highly conserved among sulfatases, suggesting that it might direct the generation of this unique amino acid derivative. In the present study residues 68-86 flanking formylglycine 69 in arylsulfatase A were subjected to an alanine/glycine scanning mutagenesis. The mutants were analyzed for the conversion of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
57
0
5

Year Published

1999
1999
2010
2010

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 60 publications
(65 citation statements)
references
References 15 publications
3
57
0
5
Order By: Relevance
“…HSPG sulfation is also extracellularly regulated by Sulf1, a member of the sulfatase gene family, related to the lysosomal Nacetyl glucosamine sulfatases (Lukatela et al, 1998;Knaust et al, 1998;Robertson et al, 1992) that has been shown to modulate the activities of many growth factors and signalling molecules by regulating the sulfation status of specific HSPGs as it specifically reduces the 6-O-sulfation of HS, a component of the HSPGs. For example, FGF activity has been shown to be inhibited by Sulf1 during chick angiogenesis and in ovarian cells by removing 6-O sulfates from glucosamine residues in HS of HSPGs, required as secondary receptors for FGF2 and FGF4 function (MorimotoTomita et al, 2002;Ai et al, 2003;Lai et al, 2004;Wang et al, 2004).…”
Section: Introductionmentioning
confidence: 99%
“…HSPG sulfation is also extracellularly regulated by Sulf1, a member of the sulfatase gene family, related to the lysosomal Nacetyl glucosamine sulfatases (Lukatela et al, 1998;Knaust et al, 1998;Robertson et al, 1992) that has been shown to modulate the activities of many growth factors and signalling molecules by regulating the sulfation status of specific HSPGs as it specifically reduces the 6-O-sulfation of HS, a component of the HSPGs. For example, FGF activity has been shown to be inhibited by Sulf1 during chick angiogenesis and in ovarian cells by removing 6-O sulfates from glucosamine residues in HS of HSPGs, required as secondary receptors for FGF2 and FGF4 function (MorimotoTomita et al, 2002;Ai et al, 2003;Lai et al, 2004;Wang et al, 2004).…”
Section: Introductionmentioning
confidence: 99%
“…In Linfoblastoid and COS cells it has been found that the mature forms presents a molecular weight between 45-55 kDa. As other members of the sulfatases family, the hIDS undergo a common posttranslational modification in which a Cys or Ser residue at the active enzyme core is converted into FGly (Schmidt et al 1995;Dierks et al 1998a;Dierks et al 1998b;Knaust et al 1998;Dierks et al 1999;Waldow et al 1999). The Cys at position 84 in hIDS is co-translationally modified to formylglycine (FGly) within the endoplasmic reticulum (ER) to produce an active enzyme (von ).…”
mentioning
confidence: 99%
“…3 , and Asp 281 were replaced by codons for asparagine, and the codon for Asn 282 was replaced by that of aspartate. Mutagenesis was performed using the pAlter cloning kit (Promega Corp.), the cDNA for human ASA (11) cloned into the pAlter mutagenesis vector (12), and appropriate primers. Following mutagenesis mutant cDNAs were cloned as EcoRI fragments into the pMPSVEH vector downstream of the myeloproliferative sarcoma virus promoter.…”
Section: Determination Of Distances and Potential Hydrogen Bonds Betwmentioning
confidence: 99%
“…After selection and expansion of the clones stably expressing the mutants, sulfatases were purified from cell secretions by affinity chromatography and dialyzed against 10 mM Tris/HCl, 150 mM NaCl, pH 7.5. V max , K m , and the pH optimum of sulfatase activity of the purified sulfatases were determined using 2, 5, 10, and 20 mM pnitrocatechol sulfate as substrate as described earlier (12). All kinetic data were determined under initial rate conditions.…”
Section: Determination Of Distances and Potential Hydrogen Bonds Betwmentioning
confidence: 99%
See 1 more Smart Citation